FACTORS AFFECTING UNDERPRICING IN THE COMPANY THAT DOES IPO IN BEI PERIOD 2004-2014 - Sidarta Hermin; Werner R. Murhadi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2015)
This study aimed to analyze the factors that influence underpricing on IPO. Variables used in this research is Underwriter Reputation (RU), Auditor Reputation (RA), Company Age (AGE), firm size (SIZE), Financial Leverage (FL), Return on Equity (ROE) and Total Asset Turnover (TATO) , This study uses a quantitative approach with a model of multiple linear regression analysis. This study used a sample of companies that conduct an Initial Public Offering (IPO) in the period 2004 to 2014 that are listed in the Indonesia Stock Exchange. The number of observations used in this study were 204 observations. The results showed that the companies doing IPOs in the period 2004-2014, the variable underwriter reputation, auditor reputation, and return on equity significantly negative effect on underpricing, while variable firm age, firm size, financial leverage, and total asset turnover negative not significantly to underpricing